Motivational Autonomy and Internalized Norms - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. A key component of Self-Determination Theory (Ryan and Deci 2000), motivational autonomy conceptualizes human behavior as driven by distinct types of motivation. Behavior that reflects individuals’ own values and interests is seen as autonomous and intrinsically motivated. Behavior taken to avoid punishment and blame or to gain reward or favor among other people is seen as extrinsically motivated. This survey tool, Motivational Autonomy and Internalized Norms, includes vignettes measuring four different types of motivation, ranging from the most autonomous (intrinsic, integrated) to the least autonomous (introjected, external). We recommend the use of this tool in the design, monitoring, and evaluation of development programs aimed at improving women’s empowerment. This data study includes following files. 1. A survey document (including implementation guidelines) 2.Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.